Demand and supply of labor market: A case of UAE - Yahya Z. Alshehhi (Apstract: Applied Studies in Agribusiness and Commerce, 2016)
United Arab Emirates (UAE) witnessed a progress of growth booming since its establishment, which as result puched all economic componets to indicated a active movement in term of employment and capital investment as well. This steady economic growth has been marked by an increase in the income by the country’s citizens, both national as well as the foreign residents This paper to axamine the supply and demand of labor market in UAE. The technique used to source the data is a secondary resource and methodology employed in descriptive and analytical. The study found that, the diversification of the economy, and enhance the role of private sector increased the demand for labor as well as increased the diversification for nationalities in the country. From other side, because of diversification strategy, the foreigners labor have more numbers in total employment structure.